Iron deficiency anemia in childhood associated with intestinal parasites: hookworm and ascariasis (Research, Society and Development, 2021)
Separadas; Por; Pon Iron deficiency is the most common nutritional deficiency in the world, affecting about 2 billion people, therefore it can be defined as insufficient iron stores for the production of red blood cells, which will eventually lead to anemia. Currently, about 45% to 50% of Brazilian children suffer from the disease. When considering iron deficiency with or without anemia, these numbers can reach over 70%. Iron deficiency anemia is defined as a decrease in hemoglobin concentration due to a decrease in the body's iron stores. The aim of this study is to analyze iron deficiency anemia and hookworm enteroparasitosis and Áscaris Lumbricoides in childhood. This is an integrative review prepared from a bibliographic survey, using books and scientific articles. Databases: SCIELO, LILACS, MEDLINE and Virtual Health Library (VHL). The literature investigation will be carried out using the following descriptors: “Ascaris lumbricoide”, “hookworm”, “iron deficiency anemia. Damage caused by intestinal parasites to their carriers includes intestinal obstruction and malnutrition (l Ascaris lumbricoides), deficiency anemia of iron (hookworms) and other problems, and their clinical manifestations are generally proportional to the load of parasites transported by the individual. The prevalence of anemia and intestinal parasites found is similar to that found in developing countries, where there are almost always social inequalities and poor basic sanitation.